Aggregate Multi-Factor Productivity: Measurement Issues in OECD Countries - Balazs Egert (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper analyses for 34 OECD countries the extent to which the calculation of aggregate multi-factor productivity (MFP) is sensitive to alternative parameterisations. The starting point is the definition of MFP used in previous work in the OECD's Economics Department (e.g. Johansson et al. 2013). They include alternative MFP measures, with human capital included or excluded, with different measures of Purchasing Power Parity (PPP) exchange rates, using time-varying capital depreciation rates and different measures of capital stock and labour input (headcount against hours worked). The main result of the paper is that whether or not human capital is included in MFP makes a significant difference for the level and dynamics of MFP. At the same time, MFP measures are less sensitive to other parameters of the calculation.
Keywords: C23; C51; J20; L43; L51; O40; 330; C230; C510; J200; L430; L510; O400